2004
DOI: 10.1021/es0493446
|View full text |Cite
|
Sign up to set email alerts
|

Perfluorooctanesulfonate and Related Fluorochemicals in Human Blood from Several Countries

Abstract: Perfluorooctanesulfonyl fluoride based compounds have been used in a wide variety of consumer products, such as carpets, upholstery, and textiles. These compounds degrade to perfluorooctanesulfonate (PFOS), a persistent metabolite that accumulates in tissues of humans and wildlife. Previous studies have reported the occurrence of PFOS, perfluorohexanesulfonate (PFHxS), perfluorooctanoate (PFOA), and perfluorooctanesulfonamide (PFOSA) in human sera collected from the United States. In this study, concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

37
577
12
6

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 967 publications
(632 citation statements)
references
References 19 publications
37
577
12
6
Order By: Relevance
“…Previous studies have reported that PFOA is the PFC that occurred at the second greatest concentrations in human blood (serum and whole blood) samples (12,13,20). However, in the present study, concentrations of PFOA were fourth highest among the PFCs measured.…”
Section: Concentrations Of Pfcs In Blood Samples From Chinacontrasting
confidence: 80%
“…Previous studies have reported that PFOA is the PFC that occurred at the second greatest concentrations in human blood (serum and whole blood) samples (12,13,20). However, in the present study, concentrations of PFOA were fourth highest among the PFCs measured.…”
Section: Concentrations Of Pfcs In Blood Samples From Chinacontrasting
confidence: 80%
“…The perfluoroalkyl chains and polar head groups of PFAAs imbue the chemicals with both hydrophobic and hydrophilic properties (Kissa, 2001). PFAAs were detected in various environmental matrices, including air (Dreyer et al, 2009;Li et al, 2011b), environmental and tap water (Ahrens, 2011;Bao et al, 2012;Yamashita et al, 2005), sediment (Higgins et al, 2005) and human blood (Kannan et al, 2004). Perfluorooctane sulfonic acid (PFOS) and perfluorooctanoic acid (PFOA) were frequently detected in water and sediments due to their various direct and indirect sources (Paul et al, 2008;Prevedouros et al, 2005) and potential for long-range transport (LRT) via marine currents (Ahrens et al, 2009a;Nash et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…PFOS is chemically and thermally stable, and is considered to be the terminal degradation product of many perfluorochemicals (PFCs) (Development, 2002). Considerable concentrations of PFOS have been detected in wildlife (Kannan et al, 2001;Wang et al, 2008) and humans (Kannan et al, 2004;Yeung et al, 2006). Owing to the potential bioaccumulation and the possible negative impact on the total environment and ultimately humans (Beach et al, 2006), understanding the pathway and investigating the environmental fate of PFOS are urgent.…”
Section: Introductionmentioning
confidence: 99%